The effectiveness of video modelling in training individuals with intellectual disabilities the skill of preparing a meal in a fast-food restaurant. - Almalki, Saeed; Binomran, Nada (International Journal of Developmental Disabilities, 2026)
Video modeling (VM) is an evidence-based practice that has been used with individuals with disabilities as an intervention to acquire a variety of skills, including vocational skills. The main goal of this study is to evaluate the effectiveness of VM as an intervention tool for individuals with intellectual disabilities in learning and remembering how to prepare meals in a fast-food restaurant. To achieve this, the study used an experimental method, specifically a single-subject design with a multiple probe approach. The study sample included four individuals with intellectual disabilities who were enrolled in a training and rehabilitation institution. The findings of the study found that VM is an effective intervention tool to help individuals with intellectual disabilities learn meal preparation skills in fast-food settings. The results indicated a correlation between using VM techniques and gaining these important skills. Additionally, the participants were able to remember what they learned for more than two weeks after stop using the intervention. The study provides practical suggestions for using VM in training and rehabilitation programs for individuals with intellectual disabilities.